Non-lethal roles of the initiator caspase Dronc in Drosophila - Dominguez, Daniela; Fan, Yun (Frontiers in Cell Death, 2023)
The role of caspases, or cysteine-aspartic proteases, in apoptosis has been well-studied across multiple organisms. These apoptotic caspases can be divided into initiator and effector caspases, with the former cleaving and activating the latter to trigger cell death. However, emerging evidence is supporting non-lethal roles of caspases in development, tissue homeostasis and disease. In comparison to effector caspases, less is known about the non-apoptotic functions of initiator caspases because of their more restricted activities and fewer known substrates. This review focuses on some recent findings in Drosophila on non-lethal roles of the initiator caspase Dronc. We discuss their biological importance and underlying regulatory mechanisms. Deciphering the non-apoptotic functions of Dronc will provide valuable insights into our understanding of the multifaceted functions of caspases during development and in diseases including cancer.